Determination of optimum conditions for xylanase production by Aspergillus niger using solid state fermentation - Al-Sa’ady, Ali J. R. (Iraqi Journal of Science, 2022)
Aspergillus niger is one of the most important filamentous fungi that used in the fermentation industry. Aspergillus niger isolate was cultured on potato-dextrose agar (PDA) for activation, and the optimum conditions for xylanase production from this local isolate were studied by solid state fermentation, using a medium composed of wheat bran moisten with corn steep liquor at ratio 1:0.5 (v:w) at initial pH 5.5, inoc-ulated with 1.6 × 106 spores/ml, and incubated at 30ᵒC for 5 days.